2006
DOI: 10.1158/1078-0432.ccr-06-1879
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and Clinical Effects of Injecting Mature Peptide-Loaded Dendritic Cells by Intralymphatic and Intranodal Routes in Metastatic Melanoma Patients

Abstract: Purpose: A phase I/II trial was conducted to evaluate clinical and immunologic responses after intralymphatic and intranodal injections of mature dendritic cells. Experimental Design: Fourteen patients with a metastatic melanoma received matured dendritic cells, loaded with Melan-A/MART-1and/or NA17-A peptides and keyhole limpet hemocyanin.The cells were matured overnight with Ribomunyl, a toll-like receptor ligand, and IFN-g, which ensured the production of high levels of interleukin-12p70. Dendritic cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 38 publications
2
42
0
1
Order By: Relevance
“…The frequency of antigen-specific CD8 ϩ T cells that are elicited by the combined administration of ␣CD40/TLR agonist and antigen is an order of magnitude higher than that observed with almost any other adjuvant or cell-based vaccine platform, such as antigen-pulsed DCs. [30][31][32] While the cellular and molecular basis for this striking response is incompletely understood, we have published that the expression of CD70 on DCs is critical for CD8 ϩ T-cell expansion. 9 Heightened expression of CD70 on CD8␣ Ϫ DCs is induced only when both CD40 and TLR agonists are coadministered.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of antigen-specific CD8 ϩ T cells that are elicited by the combined administration of ␣CD40/TLR agonist and antigen is an order of magnitude higher than that observed with almost any other adjuvant or cell-based vaccine platform, such as antigen-pulsed DCs. [30][31][32] While the cellular and molecular basis for this striking response is incompletely understood, we have published that the expression of CD70 on DCs is critical for CD8 ϩ T-cell expansion. 9 Heightened expression of CD70 on CD8␣ Ϫ DCs is induced only when both CD40 and TLR agonists are coadministered.…”
Section: Discussionmentioning
confidence: 99%
“…The median survival was 10.5 months. The most common adverse events included local reactions at the site of injection, and only 1 grade 4 lymphopenia occurred [121]. A study of Speiser et al exploited another synthetic TLR ligand, CpG 7909.…”
Section: Tlrs As Anti-tumor Vaccinesmentioning
confidence: 99%
“…23 Neither complete response nor partial response was observed and only two patients were stabilized for more than 3 months. They assumed that the particular type, the number and the mode of dendritic cells and the administration route might be the explanation for the limited success.…”
Section: Discussionmentioning
confidence: 92%
“…Two patients be a sign of clinical benefit. 23 Two other phase II clinical trials for metastatic melanoma reported the clinical efficiency of two different anti-CTLA-4 monoclonal antibodies, ipilimumab and tremelimumab. 24,25 The objective response rate was 4.6% (4 of 88 patients) using ipilimumab and 10% (8 of 84 patients) using tremelimumab, respectively.…”
Section: Demographicsmentioning
confidence: 99%